Morphology engineering ultrathin nitrogen-doped carbon Co-FeP derived from Co-Fe Prussian Blue Analogs for wide spectrum photocatalytic H2 evolution - Hu, Zenghui; Hao, Xuqiang; Jin, Zhiliang (Fuel (Guildford), 2023)
[Display omitted] •Co-FeP@NC cages, frames and boxes were designed via morphology engineering Co-Fe PBA.•Co-FeP@NC cages, frames and boxes have wide spectrum photocatalytic hydrogen evolution.•Surface N-doped carbon layer efficient improve the charge separation.•Morphology engineered photocatalytic activity of Co-FeP@NC.•Co-FeP@NC-4 cages exhibit the highest H2 evolution rate with AQE of 8.38 % at 520 nm. The design and development of economical, efficient and stable photocatalyst for photocatalytic hydrogen evolution is a frontier subject of sustainable energy research. In this work, a morphology engineered ultrathin nitrogen-doped carbon Co-FeP (Co-FeP@NC) derived from Co-Fe Prussian Blue Analogs (Co-Fe PBA) for wide spectrum photocatalytic hydrogen evolution. We demonstrate the versatility of a self-templated epitaxial growth strategy for construction of single-crystalline hollow nanostructured PBA (Co-Fe PBA cages, frames and boxes) with different geometries by adjusting the growth kinetics. Co-FeP@NC photocatalysts have tunable band structures by adjusted phosphating degree and all have a narrow band gap. In addition, the catalysts with different morphologies have different electronic structures, and surface nitrogen-doped carbon layer increases electron transfer rate, which makes the photocatalytic hydrogen evolution activity increase significantly. The Co-FeP@NC-4 cages exhibit the highest photocatalytic hydrogen evolution rate of 13309.4 μmol h−1 g−1 under visible light irradiation with EY as a photosensitizer and TEOA as an electron donor. Additionally, a high apparent quantum efficiency (8.38 % at 520 nm) and an excellent cycle stability was also achieved over Co-FeP@NC-4 cages. The larger specific surface area, strong light absorption ability and fast photogenerated electron-hole pairs separation efficiency of Co-FeP@NC cages may be responsible for the significantly improved photocatalytic hydrogen evolution activity. This work has provided an effective strategy for synthesis of nanostructures with different geometric topologies derived from PBA and recognizing their morphology-dependent photocatalytic activity.